Emotion dysregulation mediates the relationship between child maltreatment and psychopathology: a structural equation model - Jennissen, Simone; Holl, Julia; Wolff, Sebastian; Barnow, Sven (Child abuse & neglect, 2016)
The present study investigated the mediating effects of emotion dysregulation on the relationship between child maltreatment and psychopathology. An adult sample (N=701) from diverse backgrounds of psychopathology completed the Childhood Trauma Questionnaire (CTQ), the Difficulties in Emotion Regulation Scale (DERS), the Brief Symptom Inventory (BSI), and the negative affect subscale of the Positive and Negative Affect Schedule (PANAS) in a cross-sectional online survey. Correlational analyses showed that all types of child maltreatment were uniformly associated with emotion dysregulation, and dimensions of emotion dysregulation were strongly related to psychopathology. Limited access to strategies for emotion regulation emerged as the most powerful predictor. Structural equation modeling analyses revealed that emotion dysregulation partially mediated the relationship between child maltreatment and psychopathology, even after controlling for shared variance with negative affect. These findings emphasize the importance of emotion dysregulation as a possible mediating mechanism in the association between child maltreatment and later psychopathology. Additionally, interventions targeting specific emotion regulation strategies may be effective to reduce psychopathology in victims of child maltreatment.